Ischemic time and patient outcomes after the 2018 UNOS donor heart allocation system change. Issue 9 (9th June 2022) - Siddiqi, Umar; Lirette, Seth; Hoang, Ryan; Cruz, Jennifer; Mohammed, Asim; Copeland, Jack; Baran, David A.; Copeland, Hannah
Abstract: Background: The allocation system for heart donors in the United States changed on October 18, 2018. The typical distance from donor hospitals to recipient hospitals has increased as has the ischemic time. We investigated patient outcomes with the new allocation system and the differential effects of ischemic time under both the old and new allocation schemas. Methods: The United Network for Organ Sharing Registry (UNOS) was queried for data regarding heart transplants occurring from October 1, 1987 to March 1, 2021. In total, 62, 301 adult heart transplants were examined. Survival outcomes at 30 days and 1 year and ischemic times were compared via adjusted logistic and Cox models (overall survival and time until post‐transplant rejection). Results: Mean ischemic time was slightly increased in the new system (3.43 h vs. 3.03 h, p  < .001). Survival differences between old versus new systems were not observed in adjusted models ( p  = .818). However, there was evidence to suggest longer ischemic times are more detrimental to long‐term survival under the new system (hazard ratio [HR] = 1.15 per hour increase; p  = .001) versus the old system (HR = 1.08 per hour increase; p  < .001), although this relationship did not reach statistical significance ( p  = .150). Conclusions: Although travel distances have significantly increased under the new allocation system, survival outcomes remain largely unchanged. Ischemic time is an influential factor in recipient survival that should be limited during organ transport. Further studies on the impact of travel distances and ischemic time under the new allocation system are needed.